1997
DOI: 10.1677/joe.0.1550577
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of leptin removal from the circulation by the kidney

Abstract: This study was performed to test the hypothesis that the kidneys play a primary role in the clearance of endogenous leptin from the circulation. Lean male Sprague-Dawley rats were anesthetized and subjected to various surgical manipulations of the kidneys. Sixty minutes after surgery arterial blood samples were taken at 1-h intervals for up to 8 h. Plasma leptin levels were determined by radioimmunoassay. Bilateral nephrectomy induced a rapid increase in plasma leptin concentrations above control values, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
97
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 20 publications
(16 reference statements)
8
97
1
4
Order By: Relevance
“…These short-term variations were likely to reflect changes in secretion rather than clearance. Leptin is rapidly cleared from the circulation by renal extraction, which is a high capacity, non-saturable process (Cumin et al 1997, Zeng et al 1997. Like Blache et al (2000), we found no evidence for a diurnal rhythm of plasma leptin in sheep occurring independently from the timing of meals, in either photoperiod.…”
Section: Discussioncontrasting
confidence: 60%
“…These short-term variations were likely to reflect changes in secretion rather than clearance. Leptin is rapidly cleared from the circulation by renal extraction, which is a high capacity, non-saturable process (Cumin et al 1997, Zeng et al 1997. Like Blache et al (2000), we found no evidence for a diurnal rhythm of plasma leptin in sheep occurring independently from the timing of meals, in either photoperiod.…”
Section: Discussioncontrasting
confidence: 60%
“…Adipose tissue production, renal clearance, and hepatic metabolism are important determinants of the serum leptin level [44, 45, 46, 47]. As GH receptors are present and functional in all three tissues [48, 49, 50, 51, 52, 53], there is no definite indication as to the mechanism of GH downregulation of the leptin axis.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that endogenous leptin is cleared from the circulation in the kidney by glomerular ®ltration, followed by metabolic degradation in the renal tubules of Zucker (faafa) 19 and Sprague ± Dawley rats. 20,21 In humans, circulating leptin concentrations are related to the degree of renal function, assessed by 1aplasma creatinine. 22 In contrast, it has been recently reported that intact leptin is increased in patients with end-stage renal disease, although increased production may account for the high concentrations of leptin.…”
Section: Introductionmentioning
confidence: 99%